2021
DOI: 10.1007/978-1-0716-0978-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Photoacoustic Imaging of the Kidney: Basic Concepts and Protocols

Abstract: Noninvasive, robust, and reproducible methods to image kidneys are provided by different imaging modalities. A combination of modalities (multimodality) can give better insight into structure and function and to understand the physiology of the kidney. Magnetic resonance imaging can be complemented by a multimodal imaging approach to obtain additional information or include interventional procedures. In the clinic, renal ultrasound has been essential for the diagnosis and management of kidney disease and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Acute kidney injury (AKI) is one of the most common problems in critically ill patients in the clinic as well as one of the adverse prognostic factors [ 1 ]. AKI can be caused by various factors, such as hypovolemia, shock, major surgery, trauma, and heart failure, of which sepsis is the most common [ 2 ]. AKI patients generally need to be admitted to the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is one of the most common problems in critically ill patients in the clinic as well as one of the adverse prognostic factors [ 1 ]. AKI can be caused by various factors, such as hypovolemia, shock, major surgery, trauma, and heart failure, of which sepsis is the most common [ 2 ]. AKI patients generally need to be admitted to the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…The above evidence from RDUS indicated significant renal injury before the pathological confirmations. Our results suggested that, as a certain predictive indicating index in clinical practice ( Meyer et al, 2021 ), RDUS showed its advantage in evaluating renal injury in the DKD rat model. Our RDUS results also suggested that the improvement of interlobar artery PSV, MV, and EDV were consistent with the improvement of renal pathology in DKD rats after chaga intervention.…”
Section: Discussionmentioning
confidence: 63%
“…The main measurement indicators include a decline in glomerular filtration rate (GFR), an increase in albuminuria, the thickening of the glomerular basement membrane (GBM) and the presence of advanced mesangial matrix expansion, arteriolar hyalinosis, and tubulointerstitial fibrosis ( Brosius et al, 2009 ). A noninvasive, robust, and reproducible method to image arteriolar microangiopathy is provided with renal Doppler ultrasound (RDUS), which can give better insight into the structure, function, and physiology of an animal’s kidney ( Meyer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Other experiments have shown that renal function shows a significant positive correlation with PSV and EDV levels in the intrarenal artery and a negative correlation with RI and PI. 51,52 Some investigators have suggested that the change in MV should be a more sensitive indicator because MV varies with hemodynamic resistance, which is consistent with Poiseuille's law. 53 Our study showed for the first time that the parameters PSV, MV, EDV and RI and PI obtained in the interlobar renal arteries of DN rats were more significantly altered than those obtained in the main and segmental arteries.…”
mentioning
confidence: 75%